2021
DOI: 10.3389/fcimb.2021.665406
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Gut Microbial Community Structure and Function in Polycystic Ovary Syndrome With High Low-Density Lipoprotein Cholesterol

Abstract: Gut microbiota has been proved to be involved in the occurrence and development of many diseases, such as type 2 diabetes, obesity, coronary heart disease, etcetera. It provides a new idea for the pathogenesis of polycystic ovary syndrome (PCOS). Our study showed that the gut microbial community of PCOS with high low-density lipoprotein cholesterol (LDLC) has a noticeable imbalance. Gut microbiota of PCOS patients was significantly changed compared with CON, and these changes were closely related to LDLC. Gut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…A high level of cholic acid in the gut could be related to the alteration of the colonic microbiota [ 16 , 17 ]. In the present study, we obtained colonic microbial samples and assessed the colonies of the Enterobacteriaceae family from both groups, growing the bacteria on MacConkey Agar.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A high level of cholic acid in the gut could be related to the alteration of the colonic microbiota [ 16 , 17 ]. In the present study, we obtained colonic microbial samples and assessed the colonies of the Enterobacteriaceae family from both groups, growing the bacteria on MacConkey Agar.…”
Section: Resultsmentioning
confidence: 99%
“…However, some members are considered pathobionts, such as Salmonella, Shigella, and Yersinia [ 22 ]. The family has been found increased in PCOS patients [ 17 ]. Before the study, we hypothesized that Enterobacteriaceae colonies would increase under HSCA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysbiosis is a consistent finding when looking at the microbiome of women with PCOS [140][141][142][143]. Although most studies are small, dysbiosis has consistently been found to correlate with different physiological parameters, such as obesity, sex hormones and metabolic defects [140,141,143].…”
Section: Microbiome and Dysbiosismentioning
confidence: 87%
“…Several studies have reported alterations in the gut microbiota of patients with ovarian dysfunction, especially in patients with polycystic ovary syndrome (PCOS) ( 3 , 4 ). The gut microbiota may also affect metabolite levels in various metabolic pathways in patients with PCOS, especially in lipid metabolism, which, in turn, may further aggravate the imbalance of the intestinal microbiota ( 5 ). However, only one recent report identified altered microbial profiles in the gut microbiome of patients with POI.…”
Section: Introductionmentioning
confidence: 99%